Yunnanosticta gen. nov., from Yunnan, a new genus from the Sinostictinae, with the description of two new species (Odonata: Zygoptera: Platystictidae) - Dow, Rory A.; Zhang, Hao-Miao (Zootaxa, 2018)
Yunnanosticta gen. nov. in the platystictid subfamily Sinostictinae is described from Yunnan, China. The genotype is Yunnanosticta wilsoni sp. nov., described here (holotype ♂ from Tongbiguan, Yingjiang County, Dehong Dai & Jingpo Autonomous Prefecture, Yunnan, China, 23 vi 2015, leg. H.M. Zhang, to be deposited in the Natural History Museum, London). Yunnanosticta cyaneocollaris sp. nov. (holotype ♂ from Tongbiguan, Yingjiang County, Dehong Dai & Jingpo Autonomous Prefecture, Yunnan, China, 23 vi 2015, leg. H.M. Zhang, to be deposited in the Natural History Museum, London) is also described.